Commentary: Altered medial frontal and superior temporal response to implicit processing of emotions in autism. (August 2018) - Rice, Timothy
Highlights: In the recent article in Autism Research entitled "Altered Medial Frontal and Superior Temporal Response to Implicit Processing of Emotions in Autism" individuals with autism spectrum disorders (ASDs) were found to have deficits in implicit but not explicit emotion processing. This finding may inform future developments of psychotherapeutic interventions for individuals with ASDs. Specifically, interventions addressing implicit rather than explicit emotion regulation may benefit this population. Preexisting treatments including Alan Greenspan's Floor Time may promote implicit emotion regulation. The operationalization and manualization of targeted approaches to implicit emotion regulation, such as Regulation Focused Psychotherapy for Children (RFP-C), may benefit individuals with ASDs.